Lipidic matrixes containing lemon essential oil increases storage stability: rheological, thermal, and microstructural studies (2020)
ABSTRACT: Lemon essential oil (LEO) is known for having excellent antioxidant properties with applications in the pharmaceutical, food and cosmetic sectors. However, its deficient stability to light and temperature compromise this activity. In this study, waxy emulsifiers, such as beewax, candelilla wax, carnauba wax, and ozokerite wax, were employed in order to create lipidic matrixes with LEO as a continuous phase by heating to 80 ◦C under homogenization, followed by rapid cooling to 25 ◦C. The thermal, microstructural, rheological, and antioxidant tests were then conducted on such matrixes. The difference in melting, crystallization, and gelling temperatures was explained by the diverse chemical composition (long-chain wax esters in carnauba wax having a high melting point, and short-chain fatty acids and hydrocarbons in beewax and ozokerite wax, respectively). Crystal habits of these matrix systems varied from grainy, oval, to fiber-like shape, whereas there was a prevalent orthorhombic allomorph. The alignment and reorganization of carnauba and candelilla wax crystals led to an increase in the matrix strength as compared to those of beeswax and ozokerite matrixes, which showed a weak texture and poor crystallization behavior. The last two matrix systems showed the best flow and extensibility. These lipidic matrixes showed potential use for topical applications having good oil retention capacity and better antioxidant properties as compared to the raw essential oil.